2022
DOI: 10.3389/fmicb.2022.735911
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Acid Soil-Adapted Strain Rhizobium favelukesii OR191 Encodes Determinants for Effective Symbiotic Interaction With Both an Inverted Repeat Lacking Clade and a Phaseoloid Legume Host

Abstract: Although Medicago sativa forms highly effective symbioses with the comparatively acid-sensitive genus Ensifer, its introduction into acid soils appears to have selected for symbiotic interactions with acid-tolerant R. favelukesii strains. Rhizobium favelukesii has the unusual ability of being able to nodulate and fix nitrogen, albeit sub-optimally, not only with M. sativa but also with the promiscuous host Phaseolus vulgaris. Here we describe the genome of R. favelukesii OR191 and genomic features important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 94 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…Failures in Medicago sativa (alfalfa) production have been attributed to low soil pH and the presence of inefficient parasitic rhizobia strains (Eardly et al, 1992;Del Papa et al, 1999;Eardly et al, 2022). This group of rhizobia generically, known as the Oregon-like strain, are competitive for nodulation of alfalfa in acid soils but exhibits low symbiotic efficiency.…”
Section: This Research Topicmentioning
confidence: 99%
“…Failures in Medicago sativa (alfalfa) production have been attributed to low soil pH and the presence of inefficient parasitic rhizobia strains (Eardly et al, 1992;Del Papa et al, 1999;Eardly et al, 2022). This group of rhizobia generically, known as the Oregon-like strain, are competitive for nodulation of alfalfa in acid soils but exhibits low symbiotic efficiency.…”
Section: This Research Topicmentioning
confidence: 99%
“…Failures in alfalfa (Medicago sativa) production have been attributed to soil acid pH, aluminium toxicity (Bouton, 2012;Jaiswal et al, 2018;Shi et al, 2022) and the presence of parasite rhizobia strains that inefficiently nodulate alfalfa (Torres Tejerizo et al, 2011;Eardly et al, 2022). These parasite strains, known as Oregon-like, have tolerance to acidic conditions, a host broad range (Eardly et al, 1992;Del Papa et al, 1999), and its presence has also been confirmed in USA and Canada (Bromfield et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Oregon strain LPU83 has been isolated from alfalfa root nodules in Argentina and was assigned to the novel species Rhizobium favelukesii (Torres Tejerizo et al, 2016). Oregon strains are competitive for the nodulation of alfalfa in acid soils and have low symbiotic efficiency in this legume (Del Papa et al, 2003;Torres Tejerizo et al, 2011;Eardly et al, 2022). For this reason, it is important to know the presence of this type of strain in places where alfalfa is grown, as well as their competitiveness respect to the inoculant used or native efficient strains present in the soil.…”
Section: Introductionmentioning
confidence: 99%